SAT0582 Psoriasis Symptom Inventory is a Valid Patient-Reported Instrument for the Assessment of Skin Severityin Psoriatic Arthritis. (9th June 2015) - Aydın, S.Z.; Yılmazer, B.; Bayındır, Ö.; Aksu, K.; Dalkılıç, E.; Öksüz, M.F.; Tarhan, E.F.; Can, M.; Küçükşahin, O.; Kimyon, G.; Akyol, L.; Onat, A.M.; et al.
Abstract : Background: Skin involvement in psoriatic arthritis (PsA) has significant impacts on health-related quality of lives in addition to the joint involvement. Due to this impact, it's important to assess the severity of psoriasis to fully capture disease activity in PsA. In this study we aimed to test the validity of "Psoriasis symptom inventory" (PSI) in a cohort of patients with PsA. Methods: PsART (Ps oriatic A rthritis R egistry of T urkey) is a prospective, multicentre, nationwide study in Turkey on patients with PsA. Patients are consecutively recruited to this registry, if they are diagnosed as PsA, regardless of any other disease characteristics. In this registry, PSI data was available in 237 patients. For the PSI the following items were scored on a scale between 0-4, by the patient: itching, redness, scaling, burning, stinging, cracking, flaking and pain. The PSI score was calculated as a sum of these items and ranged between 0-32. The correlations between PSI and other outcome measures were investigated. Results: The mean (SD) age and BMI were 44.7 (12.3) and 28.7 (5.6), respectively. Sixty-six percent of the patients were female. The duration of psoriasis in this group was 167.3 (124.2) months. Mean (SD) PSI scores were 6.7 (6.7) with a range of 0-32. PSI scores were found to be significantly correlated to patient (R=0.338) and physician global assessments (R:0.342), fatique (R=0.226), pain (R=0.334) (p<0.001 for all comparisons) and HAQ (R=0.198; p=0.007). PSI was also correlated to body surface area involved, measured by the physician (R=0.256, p=0.07). Conclusions: PSI has a good construct validity in comparison to other clinical assessment tools. Due to its high feasibility, PSI can be a useful tool to investigate and record the severity of psoriasis in PsA in clinical practice. Disclosure of Interest: None declared